The General Theory at 80: Reflections on the History and Enduring Relevance of Keynes' Economics - Thomas I. Palley (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2017)
This paper reflects on the history and enduring relevance of Keynes? economics. Keynes unleashed a devastating critique of classical macroeconomics and introduced a new replacement schema that defines macroeconomics. The success of the Keynesian revolution triggered a counter-revolution that restored the classical tradition and now enforces a renewed classical monopoly. That monopoly has provided the intellectual foundations for neoliberalism which has produced economic and political conditions echoing the 1930s. Openness to Keynesian ideas seems to fluctuate with conditions, and current conditions are conducive to revival of the Keynesian revolution. However, a revival will have to overcome the renewed classical monopoly.
Keywords: E0; E12; B1; B2; 330; Keynes; General Theory; Keynesian revolution; Classical economics; classical counter-revolution